SETTING PERILAKU ADAPTASI PADA SEKOLAH PASCA PANDEMI DI KOTA PONTIANAK - Nurhamsyah, Muhammad Nurhamsyah; Lestari,; Muazir, Syaiful; Rudiyono,; Alhamdani, M. Ridha (Nature: National Academic Journal of Architecture, 2022)
Abstract_ The COVID-19 pandemic has brought changes in both activities and space design to prevent the wider spread of the virus. These changes need an adaptation so that activities can run smoothly. Adaptation can be in the form of changes in space design, activities, and so on. One of the activities that began to be carried out was learning at school. In this regard, the purpose of this research is to see what changes have occurred (design and regulations) and the process of human adaptation to these changes. This research was conducted on 4 objects, namely SD 14 Pontianak Kota Subdistrict, SD 56 West Pontianak Subdistrict, SMP 2 South Pontianak Subdistrict, and SMP 10 South Pontianak Subdistrict. The methodology used is place-centered mapping, interviews, and questionnaires. The results of the study showed changes in the form of physical such as the provision of handwashing facilities, temperature checking, and changes in the overall seating arrangement and space setting changes at the level of acceptance. As for non-physical changes (regulations) such as the circulation path, it shows that humans are at a level in the process (some accept and reject). This shows that humans are more receptive to changes/adaptations to physical things, while non-physical changes still allow humans to refuse and act by what they usually do. Keywords: Post Pandemic Adaptation; Pandemic Covid-19; Behaviour Setting; Post Pandemic School.